Binding of 16S rRNA to chloroplast 30S ribosomal proteins blotted on nitrocellulose - Rozier, Claude (1984)
Protein-RNA associations were studied by a method using proteins blotted on a nitrocellulose sheet. This method was assayed with Escherichia Coli 30S ribosomal components. In stringent conditions (300 mM NaCl or 20° C) only 9 E. coli ribosomal proteins strongly bound to the 16S rRNA: S4, S5, S7, S9, S12, S13, S14, S19, S20. 8 of these proteins have been previously found to bind independently to the 16S rRNA. The same method was applied to determine protein-RNA interactions in spinach chloroplast 30S ribosomal subunits. A set of only 7 proteins was bound to chloroplast rRNA in stringent conditions: chloroplast S6, S10, S11, S14, S15, S17 and S22. They also bound to E. coli 16S rRNA. This set includes 4 chloroplast-synthesized proteins: S6, S11, S15 and S22. The core particles obtained after treatment by LiCl of chloroplast 30S ribosomal subunit contained 3 proteins (S6, S10 and S14) which are included in the set of 7 binding proteins. This set of proteins probably play a part in the early steps of the assembly of the chloroplast 30S ribosomal subunit.